Patients’ self-assessment on orthodontic retainers – a qualitative research / Eunice Soh Xinwei - Eunice, Soh Xinwei (2019)
At the end of orthodontic treatment, a retention regimen is used to prevent relapse. Orthodontic retainers can be removable or bonded to teeth. Patients’ satisfaction regarding orthodontic retainers affects their ability and willingness to comply with the prescribed retention regimen. This study is aimed to explore the effect of the prescribed orthodontic retainers on patients’ everyday life and to explore the limitations in adhering to the prescribed orthodontic retention regimen. A qualitative study was carried out using the grounded theory approach. Purposive sampling was conducted, with subjects being orthodontic patients at the Faculty of Dentistry, University of Malaya. Individuals aged 18 years and older who were able to speak in Malay and/or English language and on a bonded or removable retention regimen for six months to two years were recruited. In-depth interviews (IDI) and three focus group discussions (FGD) – Hawley retainer group, thermoplastic retainer (VFR) group and a mixed group (removable and bonded retainers) were conducted. All responses were tape-recorded and transcribed. Framework analysis was undertaken to determine emerging themes. Six IDIs with three male and three female participants aged 18 to 24 years were conducted until a saturation point was reached. All three FGDs with participants aged 18 to 37 years had more female than male participants. Emerged themes on the effects of retainers on patients’ everyday life were speech interference, eating disturbance, the appearance of the retainers, difficulty cleaning, uncertainty on storing removable retainers, the need to bring removable retainers when going away, and the need to get bonded retainers checked. Emerged themes on limitations in adhering to the retention regimen were remembering to take removable retainers when going away, lost removable retainers, interfered eating habit, retainer cleaning and cleanliness, and lack of incentive to wear removable retainers when already wearing bonded retainers. These iv themes can form a conceptual framework for the future development of a validated questionnaire regarding patient satisfaction to orthodontic retention. Night-only removable retainer wear regimen eliminates the embarrassment of speaking, eating, and appearing with retainers in public. Personalised orthodontic retention prescription suiting the individual patient’s lifestyle and needs may improve patient satisfaction and compliance to retention regimen. Keywords: Orthodontic retainers, removable retainers, bonded retainers, patient satisfaction, qualitative research